2021
DOI: 10.1016/j.jsps.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between serology and nucleic acid amplification test in blood donors who are reactive for hepatitis B virus, hepatitis C and human immunodeficiency virus and evaluation of the epidemiological profile of infected people in blood centers in the State of Paraná

Abstract: Objectives To compare the results of conventional serological tests and molecular technology (NAT, Nucleic Acid Amplification Test), identify donors in the diagnostic window period, and determine the prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) among the samples of blood donors blocked by serological screening. Methods A retrospective cross-sectional study was carried out by analyzing blood donor information cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
0
1
Order By: Relevance
“… 25 , 28 It has been reported that the HIV prevalence among first blood donors greatly exceeded that in repeat blood donors. 26 , 29 In this study, we observed the same trend in 2019, but in 2020, the prevalence of HIV among repeat blood donors decreased and the prevalence of HIV among first-time blood donors was higher than that among repeat blood donors in 2021. We also found that COVID-19 had a significant effect on the proportion of first-time and repeat blood donors, it was the first time in 2020 that there were more repeat blood donors than first-time blood donors from 2013 to 2021.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“… 25 , 28 It has been reported that the HIV prevalence among first blood donors greatly exceeded that in repeat blood donors. 26 , 29 In this study, we observed the same trend in 2019, but in 2020, the prevalence of HIV among repeat blood donors decreased and the prevalence of HIV among first-time blood donors was higher than that among repeat blood donors in 2021. We also found that COVID-19 had a significant effect on the proportion of first-time and repeat blood donors, it was the first time in 2020 that there were more repeat blood donors than first-time blood donors from 2013 to 2021.…”
Section: Discussionsupporting
confidence: 67%
“…19,20,22,23 Some researchers' conclusions mean that HIV is related to lower education levels, 21,22,24,25 but others mean that the prevalence of HIV among blood donors with >8 years of education was higher than those with < 8 years of education. 23,26 However, in our results, we did not find significant differences in the HIV prevalence between higher-educated blood donors and lower-educated blood donors and the impact of COVID-19 on the HIV prevalence in these two groups. We only found that the percentage of blood donors with a higher educational background increased in 2020.…”
contrasting
confidence: 82%